Latihan Auditori Pada Anak dengan Gangguan Pendengaran: Studi Kasus Tunggal - Deni Alamsyah; Nadifa Ramadhanti; Ricky Rahman; Bayu Purnomo (Jurnal Terapi Wicara, 2023)
verbal communication is studied primarily through the auditory modality. Adverse impact on language development, cognition, academics, including verbal communication when there is a decrease in hearing sensitivity. Hearing loss will result in a reduced ability to understand and produce intelligible speech.